Combustion of pulverised coal in a mixture of oxygen and recycled flue gas - Toporov, Dobrin (Elsevier, 2014)
Combustion of Pulverised Coal in a Mixture of Oxygen and Recycled Flue Gas focuses on a niche technology, combustion of coal in an oxygen rich environment, which is one approach to obtaining 'clean coal, ' by making it easier to capture carbon that is released in the combustion process. Toporov's book breaks ground on covering the key fundamentals of oxycoal technologies, which have not yet been covered in this depth. Combustion of Pulverised Coal in a Mixture of Oxygen and Recycled Flue Gas summarizes the main results from a pioneering work on experimental and numerical investigations of oxyfuel technologies. It provides the theoretical background of the process, the problems to be faced, and the technical solutions that were achieved during these investigations.